Efficacy of different modes in disseminating Potential Fishing Zone (PFZ) forecasts - a case study from Andaman and Nicobar Islands - George, Grinson; Sarma, Kamal; Bharathi, Goutham; Kaliyamoorthy, Muthuraj; Krishnan, Pandian; Kirubasankar, R (Indian Journal of Fisheries, 2013)
Potential Fishing Zone forecasts based on Indian Remote Sensing satellite P4 Ocean Colour Monitor derived chlorophyll concentration and National Oceanographic Aerospace Administration-Advanced Very High Resolution Radiometer derived sea surface temperature were disseminated through different modes viz., Digital display boards, e-mail, telephoning/text messaging, radio, community networking and distribution of print-outs in person to the targeted fishermen and the efficacy was tested. Profound reach of technology dissemination was observed in telephoning/text messaging with an average of 72 users per forecast. Printouts of PFZ maps were distributed to an average of 35 fishermen/boat-masters in person. Digital Display Boards were viewed by 30 fishermen per forecast. E-mail message containing PFZ forecasts were sent to regional fisheries sub-stations of remote islands and it was inferred that an average of 15 fishermen per forecasts were benefitted. Further, PFZ messages were transmitted through All India Radio and Agromet Field Unit for extensive reach all along the inhabited islands. Since the validity period of PFZ forecasts is limited to 2-3 days, near real-time dissemination through telephoning/text messaging was found as an optimal tool for efficient utilisation. Field level constraints in different dissemination modes are illustrated in the paper.